2010
DOI: 10.1007/s00044-010-9354-x
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and in vitro antibacterial and antifungal activities of some novel spiro[azetidine-2,3′-indole]-2,4(1′H)-dione

Abstract: The present study deals with the synthesis of novel spiro[azetidine-2,3 0 -indole]-2 0 ,4(1 0 H)-dione derivative from the reactions of 3-(phenylimino)-1,3-dihydro-2H-indol-2-one derivatives with chloracetyl chloride in the presence of triethylamine (TEA). All the compounds were characterized using IR, 1 H-NMR, MS, and elemental analysis. They were screened for their antibacterial and antifungal activities. The bacterial strains used were Grampositive Staphylococcus aureus (MTCC-96) and Gramnegative Escherichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…It was also observed among all of the prepared compounds that o‐ and p ‐nitro‐substituted phenyl groups at position 1 of the monocyclic β‐lactam core increased the antibacterial activity against all tested bacterial strains. The potent compounds 155 and 156 thus inhibited S. aureus , E. coli , and P. aeruginosa with MIC values of 6.25 μg/mL, comparable with the well‐known penicillin amoxicillin and aminoglycoside gentamicin …”
Section: N1‐aromatic or N1‐heterocyclic Substituted Monocyclic β‐Lactamsmentioning
confidence: 74%
See 1 more Smart Citation
“…It was also observed among all of the prepared compounds that o‐ and p ‐nitro‐substituted phenyl groups at position 1 of the monocyclic β‐lactam core increased the antibacterial activity against all tested bacterial strains. The potent compounds 155 and 156 thus inhibited S. aureus , E. coli , and P. aeruginosa with MIC values of 6.25 μg/mL, comparable with the well‐known penicillin amoxicillin and aminoglycoside gentamicin …”
Section: N1‐aromatic or N1‐heterocyclic Substituted Monocyclic β‐Lactamsmentioning
confidence: 74%
“…The potent compounds 155 and 156 thus inhibited S. aureus, E. coli, and P. aeruginosa with MIC values of 6.25 μg/mL, comparable with the well-known penicillin amoxicillin and aminoglycoside gentamicin. 188…”
Section: N1-aromatic or N1-heterocyclic Substituted Monocyclic β-Lactamsmentioning
confidence: 99%
“…Compounds of this family were tested for antibacterial and antifungal activities with good results [23]. Spiro compound 12 with an indoline moiety showed good antifungal and antibacterial activity with MIC value of 6.25-12.5 μg/ml against three evaluated bacterial strains [24]. Structure-activity relationship study of these spiro-fused azetidinones showed that the presence of electron withdrawing group substitution on indoline ring and on N-phenyl ring increases both antibacterial and antifungal activity of the compound.…”
Section: -Chloro-azetidinonesmentioning
confidence: 99%
“…Some 3-amido-azetidinones were tested as inhibitors of cat K. They are characterized by a cyclic moiety on the C-3 side chain (24) which have proven to be crucial to achieve selectivity over other cathepsins [37]. The proposed mechanism of inhibition of cat K by 3,4-disubstituted azetidin-2-ones is depicted in Scheme 3 [38].…”
Section: -Amino-azetidinonesmentioning
confidence: 99%
“…The chemistry of spiro indoles in which an indole ring is joined to nitrogen containing heterocycles at C‐3 position through a spiro carbon atom has aroused great interest due to their physiological and biological activities . Amongst these spiro[azetidine‐indole] are known to possess antimicrobial activity . It was therefore, presumed that the title molecules incorporating indole, azetidinone, and triazole moieties would have enhanced biological properties.…”
Section: Introductionmentioning
confidence: 99%